Bile acid signaling mediates gut microbiota regulation of host lipid metabolism - Liu, Mengkuan; He, Cuimei; Lv, Xinyu; Zheng, Wanru; Yin, Jie; Li, Yixing; Ma, Jie (Frontiers in Microbiology, 2026)
Although advancements in the study of gut microbiota have clarified the close association between gut microbiota and the host's metabolism, the underlying mechanism remains unclear. Bile acids are important components of the host's metabolism and are deeply influenced by gut microbiota. In recent years, significant progress has been made in the study of how gut microbiota regulate their host's lipid metabolism through bile acids. This review summarizes the enterohepatic circulation of bile acids, the interaction between gut microbiota and bile acids, and the role of gut microbiota-bile acid signaling in the regulation of lipid metabolism. Finally, this review examines the effects of bile acid metabolism disorders on obesity. This review aims to provide a novel perspective for understanding the relationship between gut microbiota and the host's lipid metabolism.